THE EFFECTIVENESS OF USING SCATTERGORIES GAMES TOWARDS STUDENTS’ VOCABULARY AT MTs BAHARUDDIN TAPANULI SELATAN - MARSELINA TAMBA, SUSI (Faculty of Tarbiyah nad Teacher Training, 2021)
This study aims to determine the effect of the scattergories games toward students’ vocabulary observed and conducted at MTs Baharuddin Tapanuli Selatan. This research was conducted using quasi experimental research design. The populations in this research are students of seventh grade MTs Baharuddin Tapanuli Selatan. And the sample of this research was all of the students of second grade MTs Baharuddin because the total number of the population less than 0ne hundred students. In this research, the researcher using scattergories games in experimental class while in controlled class without using scattergories game. In this study, the researcher use pretest, treatment and posttest. Researcher uses SPSS v. 26 to calculate the data. In the posttest of experimental class and controlled class the researcher finds that the sig. (2 tailed) on the t-test 0.00 < 0.05, so there is significant different between controlled class and experimental class. Ha accepted and Ho rejected. It can be conclude that there is an effect towards students’ vocabulary by using scattergories game. (Key Word: Vocabulary, Scattergories Games)